Coming Home: Compassionate Presence in Prison1. (27th September 2017) - Haskin, David
Abstract: The Coming Home Project (CHP) of the Snowflower Sangha in Madison, Wisconsin is an active member of MOSES, a nonpartisan interfaith organization that works to promote systemic change for social justice issues with a focus on mass incarceration and ending the use of solitary confinement in the state's prisons and jails. To support these efforts, and to restore dignity and safety to the entire community, CHP members work to make Wisconsin's sentencing rules and laws more just and humane, increase treatment alternatives to incarceration, stop crimeless revocations back to prison, and remove barriers to employment for previously incarcerated individuals returning to their communities.